Elements of Pavement Management System: Case Study - Adam Zofka; Ramandeep Josen; Miglė Paliukaitė; Audrius Vaitkus; Tomasz Mechowski; Maciej Maliszewski (The Baltic Journal of Road and Bridge Engineering)
This paper presents the elements of a Pavement Management System with a particular focus on the initial effort to create a comprehensive data archive and its further application in four different maintenance strategies. Pavement performance indicators including longitudinal and transverse cracking as well as roughness were investigated with respect to numerous distinct factors which can be grouped into three categories, i.e. climatic, pavement structure, and traffic-related. High-quality climatic data was obtained from the national weather stations in Connecticut. Maintenance and construction data was used to determine the pavement age and structure amongst several other factors. Traffic data was acquired from the state records and accumulated traffic loading was estimated for all segments based on their age. High definition pavement images collected by the Automatic Road Analyzer vehicle in 2010 were used to quantify the longitudinal and transverse cracking with respect to their location within the pavement surface. Elements of the Pavement Management System with stochastic elements were created from this data and analyzed in order to demonstrate the budget implications under four different management scenarios. Scenarios varied by the trigger values of the Pavement Condition Index for considered maintenance treatments. The 20-year projection analysis clearly showed the benefit of repairing pavements that are still in a good condition even without considering related user-delay costs and/or vehicle-operation costs which would only heighten the differences between scenarios.